MUHAMMADIYAH DAN ADAT TANAH ULAYAT MINANGKABAU - IZA HANIFUDDIN (Institut Agama Islam Negeri Batusangkar, 2016)
Minangkaubaunese has believed the importance of land for centuries. Rules concerning with land within the life of Minangkabaunese traditionally can be said to be genuine community. Lands, as they believe, is basically a symbol of their own identity which is called ulayat. Furthermore, land is one of the institutional elements of matrilineal system which determines individual and communal integrity, and original and migrant residents to base any decision dealing with succeeding the right of particular region. According to rules, land are not to be sold or used for as a warranty the purpose of making loans. The influence of Muhammdiyah toward Minangkabau has colored the pattern and offered new model of the management of ulayat from succeeding communal to organizational communal by keeping the tradition concerning with the status of waqf and prohibition to be sold and diminished. All land assets, therefore, are in the control of business division of Muhammadiyah.Keywords: